A Review in Spoken Language Teaching - Salmia Syarifuddin; Irmawaty Hasyim (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
This paper aims to describe the types of spoken language for English Language teaching. Spoken language’ types considered to be varied and complex particularly to the country which its first language is not English. To implement the spoken language type in the subject, such speaking class, it is crucial to comprehend these types of spoken language. It is found that adjacency, turn-taking, and exchange were the most implemented types during the presenting speaking in the class. It is resolved that the vary the types applied in the class, the more the knowledge and classroom’s situation would be delighted.